Stereotactic radiotherapy using tomotherapy for early‐stage non‐small cell lung carcinoma: Analysis of intrafraction tumour motion. Issue 6 (27th April 2014) - Boggs, Drexell Hunter; Feigenberg, Steven; Walter, Robert; Wissing, Dennis; Patel, Bijal; Wu, Terry; Rosen, Lane
Abstract Introduction Intrafraction tumour motion in helical tomotherapy was investigated by comparing pre‐ and mid‐fraction CT scans in patients with early non‐small cell lung carcinoma (NSCLC) to assess the efficacy of a 7‐mm margin around gross tumour volumes (GTVs) in stereotactic body radiation therapy (SBRT). Methods Thirty patients with early‐stage NSCLC received SBRT in four or five fractions for a total of 141 treatments. A slow positron emission tomography/CT scan was fused with the simulation CT to determine the GTV. A planning target volume was created by placing an isotropic margin of 7 mm around the GTV. Data were retrospectively analyzed to assess translational tumour positional changes along the x, y and z axes and vector changes in millimeters from the pretreatment megavoltage (MV)‐CT to the mid‐fraction MV‐CT. Results Average movements for all 141 treatment days along the x, y and z axes were 0.5 ± 2.3, −0.3 ± 3.0 and 0.9 ± 3.0 mm, respectively. Average movements for each patient along the x, y and z axes were 0.5 ± 1.5, −0.2 ± 2.0 and 0.9 ± 1.9 mm, respectively. Average vector displacement was 4.3 ± 2.4 mm for all treatment days and 4.2 ± 1.7 mm for each patient. Of 141 treatments, 137 (97.2%) fell within 7.0 mm in all axes. Conclusion The addition of a 7‐mm margin to the GTV for patients receiving SBRT for NSCLC using tomotherapy is adequate to account for tumour movement. Mid‐fraction CT scans proved to be valuable in assessing intrafraction tumour motion.